ROSAI-DORFMAN DISEASE: REPORT OF A RARE CASE OF PERIPHERAL LYMPHADENOPATHY - Farouk AG; Zarami AB; Ahmadu MS; Ambe JP; Pindiga HU (Ntec Specialist, 2019)
Rosai-Dorfman disease (RDD), also called Sinus histiocytosis is an uncommon proliferative disorder of unknown aetiology. Though, the lymph node is the revelation mode of several diseases particularly in the tropics, RDD typically presents with painless bilateral lymphadenopathy in the neck associated with fever and leukocytosis, sometimes mimics lymphoproliferative disorders. Recently research has unveiled gene mutation in the tumour with potential of malignant transformation. Case report: We report case of 4 year old boy who had massive cervical lymphadenopathy with extranodal manifestation of fever. Sepsis screening was negative, while imaging showed hilar, mediastinal and mesenteric lymph nodes enlargement in addition to massive hepatomegaly. The histology is suggestive of the diagnosis of RDD. The patient was treated with corticosteroids, with remarkable remission. Conclusion: We report the clinicopathological characteristics of RDD in order to increase our awareness of its diagnosis and treatment and to re-emphasize that the disease is rare in our environment